Gendered perceptions of new mobility services - Kalakou, S.; Costa, M.; Pirra, M.; Lynce, A. R. (Gender and Equality in Transport. Proceedings of the 2021 Travel Demand Management Symposium, 2021)
Transport systems´ infrastructure and provided services affect people´s mode choices and define the users´ transport experience. This study focuses on the exploration of how perceptions of existing and new transport services vary among men and women and which potential measures can improve the users´ experiences. A survey is designed and replies from 1193 citizens of three European cities is collected. The data analysis aimed to indicate in which areas the perceptions of men and women differ. The results indicated that men have more trust in new technologies that can be used in mobility services such as autonomous vehicles while women have a positive attitude towards the inclusions of measures that can enhance security in the passenger experience, especially in the public transport sector.